Materials, mechanics and information engineering selected, peer reviewed papers from the 2014 3 rd International Conference on Chemical, Mechanical and Materials Engineering (CMME 2014), October 24-25, 2014, Riga, Latvia - Wongseedakaew, Khanittha; Luo, Qi (Applied mechanics and materials ;, 2015)
Collection of selected, peer reviewed papers from the 2014 3rd International Conference on Chemical, Mechanical and Materials Engineering (CMME 2014), October 24-25, 2014, Riga, Latvia. The 42 papers are grouped as follows:Chapter 1: Materials Science and Materials Engineering;Chapter 2: Applied Mechanics; Chapter 3: Manufacturing and Mechanical Engineering; Chapter 4: Computational Methods and Information Technologies Keyword: Materials Science and Materials Engineering; Applied Mechanics; Manufacturing and Mechanical Engineering; Computational Methods and Information Technologies The 42 papers appear in sections on materials science and materials engineering, applied mechanics, manufacturing and mechanical engineering, and computational methods and and information technologies. Among the topics are a first-principle study of the structural phase transition and electronic structures of cobalt under pressure, verifying the possibility of using secondary raw materials of tubular solar panels as fillers of polymer industrial floors, measuring physical and mechanical properties of high-speed heated casting cores, simulation analysis and experimental research on vehicle interior adaptive active noise control system, and a complicated transfer design method based on particle swarm optimization. -- Chemical engineering-- Materials science-- Mechanical engineering.